The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10544-008-9179-2
|View full text |Cite
|
Sign up to set email alerts
|

Inertial effects on flow rate spectrum of diffuser micropumps

Abstract: This study develops a diffuser micropump and characterizes its output flow rates, such as the parabola shape on the frequency domain and the affecting factors. First, an equivalent circuit using electronic-hydraulic analogies was constructed. Flow rate analysis results were then compared to experimental results to verify the applicability of the circuit simulation. The operational frequency was 800 Hz for both cases and maximum flow rates were 0.078 and 0.075 mul/s for simulation and experimental results, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…When the driving frequency is very low, it is not essential to consider the influence of the piezoelectric actuator's quality on driving characteristics, but when the driving frequency increases, the quality affects the vibration of the piezoelectric actuator [18]. On the basis of Figure 5(a), an equivalent inductance representing mass inertia is added to the fluid domain side, and the formula for calculating is [17]…”
Section: Dynamic Driving Characteristics Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the driving frequency is very low, it is not essential to consider the influence of the piezoelectric actuator's quality on driving characteristics, but when the driving frequency increases, the quality affects the vibration of the piezoelectric actuator [18]. On the basis of Figure 5(a), an equivalent inductance representing mass inertia is added to the fluid domain side, and the formula for calculating is [17]…”
Section: Dynamic Driving Characteristics Optimizationmentioning
confidence: 99%
“…If the depth of the cone tube is 2c, assuming that the width of an infinitely short cone tube is constant, the flow resistance of this infinitely short cone tube can be obtained, According to the definition of the cone tuber's rectification efficiency, the flow resistance of the nozzle is [18] …”
Section: Diffuser and Nozzlementioning
confidence: 99%
“…2. Note that the electrical formulae used in the simulations to model the hydraulic resistance (R hyd ), inertance (I hyd ) and capacitance (C hyd ) of the various elements within the micropump are presented in Bourouina and Grandchamp (1996), Morganti et al (2005), Hsu and Le (2008) and are therefore omitted here with two considerations that, first, the epoxy layer was considered in the present simulation. Its mass contributes to the membrane inductance as follow (Morganti et al 2005), (Hsu and Le 2008),…”
Section: Equivalent Electrical Circuit Of Micropumpmentioning
confidence: 99%
“…Bourouina and Grandchamp (1996) demonstrated the feasibility of modeling membrane micropumps with two integrated checkvalves using an equivalent electrical network. In more recent studies (Morganti et al 2005) and our lab (Hsu and Le 2008) applied an electronic-hydraulic analogy to convert a valve-less diffuser micropump system into an equivalent electrical circuit and then used the SPICE (simulation program with integrated circuit emphasis) analog circuit package (CircuitMake 6.2 Pro) to analyze its performance and dynamic response. However, to our knowledge, peristaltic micropump (Smits 1990) has not been modeled neither by CFD or equivalent electrical network by mean of the whole system operation due to its excessively complex operation structure.…”
Section: Introductionmentioning
confidence: 99%
“…actuator, passive plate, bonding layer thickness) to actuator-membrane performance was reported by Li and Chen (2003) and they showed that the structure thickness significantly affect the actuator-membrane performance and need to be optimized; therefore, thickness consideration was not included to avoid the repeated work. Furthermore, as reported by other researches (Hsu and Le 2008;Lin et al 2007), the actuatormembrane's natural frequency (i.e. resonant frequency) is approximately three order higher than the pump's maximum flow rate frequency; therefore, the impedance curves were not included in the present study.…”
Section: Introductionmentioning
confidence: 98%